A Novel Bacteriocin Against Shigella flexneri From Lactiplantibacillus plantarum Isolated From Tilapia Intestine: Purification, Antibacterial Properties and Antibiofilm Activity - Jiang, Yu-Hang; Xin, Wei-Gang; Zhang, Qi-Lin; Lin, Lian-Bing; Deng, Xian-Yu (Frontiers in Microbiology, 2022)
Few bacteriocins with antibacterial activity against Shigella flexneri have been reported. Here, a novel bacteriocin (LFX01) produced by Lactiplantibacillus plantarum strain LF-8 from the intestine of tilapia was purified and extensively characterized. LFX01 possesses a molecular weight of 1049.56 Da and an amino acid sequence of I-T-G-G-P-A-V-V-H-Q-A. LFX01 significantly inhibited S. flexneri strain 14 (S. flexneri_14) growth. Moreover, it exhibited excellent stability under heat and acid-base stress, and presented sensitivity to a variety of proteases, such as proteinase K, pepsin, and trypsin. The minimum inhibitory concentration of LFX01 against S. flexneri_14 was 12.65 μg/mL, which was smaller than that of most of the previously found most bacteriocin. Furthermore, LFX01 significantly inhibited (p < 0.05) S. flexneri_14 cells and decreased their cell viability. In addition, LFX01 could significantly (p < 0.05) inhibit biofilm formation of S. flexneri_14. Scan electron microscopy analysis presented that the cell membrane permeability of S. flexneri_14 was demolished by LFX01, leading to cytoplasmic contents leakage and cell rupture death. In summary, a novel bacteriocin of lactic acid bacteria was found, which could effectively control S. flexneri in both planktonic and biofilm states.